Peningkatan Keterampilan Santripreneur melalui Pelatihan Kewirausahaan Berbasis Digital Marketing di Kabupaten Garut - Iman Saifullah; Anton, Anton (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
The Optimizing technology in the digital era is the key to success in opening up opportunities to develop students' independence in the field of entrepreneurship. Students must be more creative in utilizing information technology. It is hoped that students and Islamic boarding schools will be able to build independence in the field of entrepreneurship through unlimited activities and creativity in accordance with the times. For this reason, Islamic boarding schools must create strategies to equip students with various skills so that they are able to produce students who are pious, have good morals, and are successful in entrepreneurship. Therefore, as a form of social concern, lecturers are required to be present in providing solutions in society. Starting with a study of the problem, data collection, planning activities and implementing mentoring activities for students to improve their digital marketing-based entrepreneurial skills. The mentoring agenda for students was carried out for as many as 50 (fifty) students, starting with interviews to explore participants' needs and ending with the implementation of digital marketing-based entrepreneurship training. This training activity invites entrepreneurship and digital business practitioners to develop students to have entrepreneurial skills by using digital as part of a marketing development strategy for the products produced, so that the marketing reach is wider and greater. This of course has implications for improving the economy of students' families.